Culturally Responsive Mathematics Education: Utilizing the Traditional Paser Game as A Promising Context in Teaching Probability and Statistical Concepts - Nada Auliya Rahmah; Rully Charitas Indra Prahmana; I Putu Ade Andre Payadnya; Dwi Astuti (Universitas Papua, 2025)
Despite the growing recognition of ethnomathematics in enriching student learning experiences, few studies have explored the mathematical content, particularly probability and statistics, embedded within specific indigenous Javanese games. This research addresses this oversight by focusing on the traditional game of Paser, an ancestral practice from Yogyakarta, offering a unique empirical bridge between local cultural philosophy and advanced mathematical concepts. The study aims to systematically identify and analyze the representations of probability and statistical reasoning inherent in the Paser gameplay. Data were rigorously gathered through ethnographic methods, specifically using participant observation, documentation, and semi-structured interviews with cultural practitioners. The findings demonstrate that Paser effectively integrates elements of probability, statistical distribution, and symbolic meaning. A key discovery is the profound link between the Javanese philosophy of hening-hening (inner calm) and an intuitive strategic approach to managing statistical variability, showcasing a deep integration of cultural values and mathematical reasoning. These insights highlight Paser's substantial potential as a contextual medium for developing culturally responsive mathematics education. By situating probability and statistics within a familiar cultural practice, this study not only contributes significantly to the ethnomathematics literature but also provides a tested model for strengthening students' appreciation of their cultural heritage alongside their mathematical literacy.